Housing the Poor The Right to the City and Policy Arrangements in Urban Indonesia - Obermayr, Christian (Franz Steiner Verlag, 2023)
This book analyses in detail half a century of international discussions on housing, slums and informal settlements, identifies policy phases (self-help, enabling) and discusses pros and cons of applied measures globally and in the context of Indonesia. It contributes to a better understanding of interlinkages between urban governance and housing policies by employing the analytical framework of policy arrangements, and by developing a normative compass based on Henri Lefebvre's right to the city. Empirically, it examines and compares housing strategies (social housing, resettlements, slum upgrading) and modes of governance in two case studies, the Indonesian cities Surabaya and Surakarta.